Managing Growth: Dynamics of Social Commerce for E-Food Retailers in Germany - Hautkappe, Chiara; Manske, Jonas (Journal of Social Commerce, 2024)
This study examines the opportunities and risks of social commerce in German online grocery retail by integrating E-Commerce and social media. Semi-structured interviews were conducted with experts from the fields of E-Commerce and online grocery retail, and transcription and qualitative content analysis were performed using established methods. The results indicate promising opportunities for S-Commerce, including the promotion of impulse purchases, improved customer loyalty, and increased likelihood of purchase. However, challenges also exist, such as data protection and security risks, technical implementation and integration, as well as significant resource usage. The results allow for differentiation between opportunities and risks that can be actively managed to a powerful, limited, or low degree.